The Operation of the 253rd Lithuanian Police Battalion in 1943–1944 - Bubnys, Arūnas (Genocidas ir rezistencija, 1998)
During the Nazi occupation there were formed 23 National Police Battalions in Lithuania. The history of some of those battalions has been deeply analysed and published by historians. The history of the 253rd National Police Battalion is a "blank spot" in the Lithuanian Police Battalion's history.The battalion operated 14 months: from May 1943, to August 1944. About a year it participated in fights against the Soviet and Polish partisans. The battalion distinguished itself by little losses in those fights. The servicemen of the battalion preserved discipline and fighting efficiency to the end of its existence. Except the fact, that the battalion participated in some forced labour round-ups organised by the Nazis in Švenčioniai district, it did not commit any major war crime. The battalion did not participate the persecution or annihilation of either Jews or any other nationality civilian people.
Keywords: German occupation; police batallions; collaboration; antinazi resistance; Soviet partisans; Polish partisans